Yellow Vests: Anti-austerity, pro-democracy, and popular (not populist) - Carpenter, Michael J.; Perrier, Benjamin (Frontiers in Political Science, 2023)
In the context of neoliberalism and its consequences for the economy and for democracy, this article offers a distinct framing of the political nature of the French “Yellow Vests” (Gilets Jaunes) movement. Fundamentally, the movement should be understood as a popular and radically democratic response to the growing social inequalities of top-down austerity governance. The movement, which began in 2018, was spontaneous, autonomous, and decentralized, made up primarily of loosely connected citizen networks and popular committees not bound by political affiliation, social class, or age group. Responding to the neoliberal policies of the government of President Emmanuel Macron, symbolized by an unpopular fuel tax, the Yellow Vests quickly developed into a wide-ranging movement with diverse forms of action and organization. Despite a carrot-and-stick response from the government, the movement continues to the present, though its impact was greatest in the first year, which is the focus of this paper. Difficult to classify, we understand the Yellow Vests as an instantiation of “popular politics”, or an atypical social movement, primarily defined by and significant for its ardent anti-austerity and pro-democracy positions. The movement is only misleadingly labeled populist or associated with populism; there is a collective intellectual awakening of political consciousness, with participants and supporters articulating their structural dispossession and setting out to strengthen their common good through collective action and more direct democracy, not through party politics or existing institutions, nor through charismatic leadership or other forms of centralized or top-down politics. The Yellow Vests therefore signify the prospect of democratizing democracy, or re-democratizing democracy, in the face of the legitimacy deficits of neoliberal governance.